The HCV Envelope Glycoprotein Down-Modulates NF-κB Signalling and Associates With Stimulation of the Host Endoplasmic Reticulum Stress Pathway - McKay, Lindsay G. A.; Thomas, Jordan; Albalawi, Wejdan; Fattaccioli, Antoine; Dieu, Marc; Ruggiero, Alessandra; McKeating, Jane A.; Ball, Jonathan K.; Tarr, Alexander W.; Renard, Patricia; Pollakis, Georgios; Paxton, William A. (Frontiers in Immunology, 2022)
Following acute HCV infection, the virus establishes a chronic disease in the majority of patients whilst few individuals clear the infection spontaneously. The precise mechanisms that determine chronic HCV infection or spontaneous clearance are not completely understood but are proposed to be driven by host and viral genetic factors as well as HCV encoded immunomodulatory proteins. Using the HIV-1 LTR as a tool to measure NF-κB activity, we identified that the HCV E1E2 glycoproteins and more so the E2 protein down-modulates HIV-1 LTR activation in 293T, TZM-bl cells and the more physiological relevant Huh-7 liver derived cell line. We demonstrate this effect is specifically mediated through inhibiting NF-κB binding to the LTR and show that this effect was conserved for all HCV genotypes tested. Transcriptomic analysis of 293T cells expressing the HCV glycoproteins identified E1E2 mediated stimulation of the endoplasmic reticulum (ER) stress response pathway and upregulation of stress response genes such as ATF3. Through shRNA mediated inhibition of ATF3, one of the components, we observed that E1E2 mediated inhibitory effects on HIV-1 LTR activity was alleviated. Our in vitro studies demonstrate that HCV Env glycoprotein activates host ER Stress Pathways known to inhibit NF-κB activity. This has potential implications for understanding HCV induced immune activation as well as oncogenesis.